Sexed animals in Swedish Southern Tradition rock carvings: gender, sexuality, fertility, and implications for animals in Bronze Age ontology. (3rd April 2019) - Lawrence, J. M.
ABSTRACT: In figurative Southern Tradition Scandinavian rock art from the Bronze Age (1700–500 cal. BC), animals of several species are, like humans, clearly and intentionally depicted with phalluses. Recently, rock art research has provided insight into the nature of gender and sexuality in Scandinavian Bronze Age ontology; however, this line of inquiry has so far been limited to anthropomorphic subjects. Through a consideration of the spatial relationships of animals with phalluses to other motifs in the carvings, this paper explores how concepts of engendering and sexualising might be fruitfully applied to depictions of animals, and engages with the question of how animal beings relate to human beings in Bronze Age ontologies.